2020
DOI: 10.1186/s13229-020-00334-5
|View full text |Cite
|
Sign up to set email alerts
|

Emerging proteomic approaches to identify the underlying pathophysiology of neurodevelopmental and neurodegenerative disorders

Abstract: Proteomics is the large-scale study of the total protein content and their overall function within a cell through multiple facets of research. Advancements in proteomic methods have moved past the simple quantification of proteins to the identification of post-translational modifications (PTMs) and the ability to probe interactions between these proteins, spatially and temporally. Increased sensitivity and resolution of mass spectrometers and sample preparation protocols have drastically reduced the large amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 155 publications
(158 reference statements)
0
19
0
Order By: Relevance
“…The expression patterns of proteins reflect the biological functions of cells better than those of mRNA or DNA; thus, it is imperative to identify protein biomarkers 4 , 5 . A large-scale study of total protein was recently conducted to identify protein biomarkers for neurodevelopment disorders 6 . The detection of protein biomarkers can be performed using brain tissues and body fluids such as cerebral spinal fluid (CSF) or serum, but diagnosis using brain tissues is not common, except in special cases.…”
Section: Introductionmentioning
confidence: 99%
“…The expression patterns of proteins reflect the biological functions of cells better than those of mRNA or DNA; thus, it is imperative to identify protein biomarkers 4 , 5 . A large-scale study of total protein was recently conducted to identify protein biomarkers for neurodevelopment disorders 6 . The detection of protein biomarkers can be performed using brain tissues and body fluids such as cerebral spinal fluid (CSF) or serum, but diagnosis using brain tissues is not common, except in special cases.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics has long played an indispensable role in the discovery and verification of biomarkers for brain disorders [ 17 ], and studies are increasingly oriented towards exploring the pathological mechanisms underlying various brain disorders. In a recently published work, researchers found that the astrocytic cystine/glutamate antiporter system xc(-) regulated corticostriatal neurotransmission, and influenced social preference and repetitive behavior in mice, providing important clues toward the neural mechanisms related to ASD and obsessive–compulsive disorder [ 226 ].…”
Section: Trends In Neuroproteomicsmentioning
confidence: 99%
“…We scrutinize the synaptic proteome in a functional context, look into the molecular mechanisms underlying brain disorders, and discuss the current opportunities, challenges, and trends in neuroproteomics. Proteomics approaches are widely used in the search for biomarkers of neurological and psychiatric disorders; however, these studies are beyond the scope of this review, and interested readers are referred to a recent review for an overview of this research field [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, transcriptome analysis using RNA-sequencing of post mortem brains has found significant changes in synaptic as well as translation, immune, chromosome, and splicing-associated genes (Quesnel-Vallières et al, 2019). In contrast, the correlation between RNA and protein amounts is not always consistent (Murtaza et al, 2020). Thus, researchers must be cautious when interpreting the results of these experiments and carefully understand the differences between these methods.…”
Section: Proteomi C S Of a S Dmentioning
confidence: 99%